The long-forgotten melody? Music in the Mesolithic - Morley, I (Oxbow Books, 2005)
The Upper Palaeolithic in Europe sees the first incontrovertible archaeological evidence for musical behaviour in humans, in the form of bone items which have been variously interpreted as flutes, pipes or whistles. In addition, there are items which may be interpreted as rasps and bullroarers, as well as evidence for the use of the natural acoustic environment. The earliest widely accepted examples of flutes are from Geissenklösterle in Germany, and are radiocarbon dated to around 37,000 BP (Hahn & Münzel 1995). Further examples of such flutes occur in the Aurignacian, the Gravettian and Perigordian, the Solutrean (although much less commonly), and the Magdalenian periods, and occur throughout Europe, at sites in Germany, Belgium, the Balkans, the French Pyrenees and Dordogne, amongst many others. The literature regarding these artefacts is expansive, spanning the 19th and 20th centuries, although it has at times been rather over-enthusiastic in its attribution of functionality to the evidence. The Mesolithic appears to be a complete contrast. In the literature, at least, there appears to be a relative scarcity of musical material afterthe Magdalenian (18,000– 12,000 years ago) in the immediate post-glacial of Mesolithic Europe. Not only is there considerably less material with obvious musical provenance, there is virtually no mention, let alone discussion, of musical behaviour in the literature relating to the Mesolithic (with the notable exceptions of Beltrán (1982) and Mithen (1994) who refers to Beltrán). Why, after at least 25,000 years of instrumental musical behaviour with many sophisticated artefacts such as those found at Isturitz, Le Roc De Marcamps, and Le Placard (e.g. Seewald 1934; Saint-Perier & Saint-Perier 1952; Rousot 1970) which surpass even mediaeval examples in their manufacture (Scothern 1992), is there a relative dearth of evidence of such activity in the Mesolithic? Is it an issue of the choice of raw materials being used for the manufacture of such objects, and their preservation? Is it that such activities were no longer being performed? Indeed, is there a true scarcity of evidence, or is the evidence simply not wellrepresented in the literature? These are questions to which this chapter may go some way to answering, but only more detailed and critical examination of these finds, and of new finds in the future, will truly shed light on these issues.